School safety and existing legal provision guiding in the context of Nepal (Siddhajyoti Interdisciplinary Journal, 2021)
Disaster has impacted the education sector in Nepal. It has disrupted the teaching and learning system with an increased dropout rate of students. Furthermore, it has shaken the resilience of the local communities. Due to this situation, children are exposed to a vulnerable situation and lack a safe learning environment. To mitigate this risk, most of the countries have adopted the comprehensive safe school framework. It is expected to be effective measures in Disaster Risk Reduction in education. In the context of Nepal, Comprehensive School Safety (CSS) legal provisions have been formulated in principle but lack its implementation at school and local level. This article explores the existing guiding provisions contributing to safe schools. The desk study was conducted on the basis of published literature and analyzed. The findings revealed that education is seriously impacted by disaster each year, and there is an inadequate implementation of the existing legal provisions at the local and school level. In addition to that, after disasters situation, school dropouts has been increased, and equal access to education has been challenged and more importantly, teaching and learning process are not continued. This has questioned the effective implementation of CSS and challenged the existing legal provision.